Panorama of transport : statistical overview of transport in the European Union: data 1970-2000. (Theme 7: Transport. Collection, Panorama of the European Union, 2002)
Summary: The Panorama of Transport sets out to describe, via statistics, the most important features of transport in the EU. It describes transport not only in terms of the quantities of freight and passengers moved and the vehicles and infrastructure used, but also as part of the economy. This second edition of the Panorama is not just a simple updating of the previous edition; It widens its coverage to include air transport , where international passenger transport has been increasing, since 1993 - the first year in which data were collected by Eurostat - at a rate equivalent to a boubling every ten years. Road freight cabotage, while remaining a small part of total national transport is also growing fast, and is therefore covered in detail.